Review and Comparison of Food Drug Administration (FDA) and Medicines and Healthcare products Regulatory Agency (MHRA) on Good Manufacturing Practice (GMP) Implementation - Farida Nur Aziza (Majalah Farmaseutik, 2022)
A government is responsible for ensuring public health and safety. One of the approaches is to establish a regulatory body that governs health-related items such as pharmaceuticals and other human health-related products. These regulatory bodies exist to ensure that goods satisfy high standards of quality, safety, and efficacy. This article investigates several aspects of regulatory bodies' regulation and Good Manufacturing Practice (GMP) standards controlled by two regulatory organizations, the Food and Drug Administration (FDA) and the Medicines and Healthcare products Regulatory Agency (MHRA). Both regulatory agencies appear to have some items controlled and fairly specific product authorization guidelines. It is apparent that both regulatory authorities have some comparable notions in common when it comes to GMP implementation, product registration, mutual recognition agreements, and MoU implementation.